Application of Dry Biomass of Aphanothece sp. as A Biosorbent of Copper Heavy Metal - Fauzi Abdilah; Lina Troskialina (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
Various technologies have been developed to reduce heavy metal content in the wastewater. The biosorption method is a technique that is widely applied because it is cheap, environmentally friendly, and has high efficiency. This study aims to ascertain the potential of dry biomass of microalgae Aphanothece sp. as a biosorbent of Cu (II) ions in synthetic wastewater and determine the appropriate biosorption kinetics model. Analysis of Cu (II) ion concentrations was carried out using Atomic Absorption Spectrophotometer (AAS). The results showed that the optimum conditions for the biosorption process were at pH 4, and the contact time was 210 minutes with the removal efficiency of Cu (II) ions reaching 80.02%. The results of tests on the adsorption isotherm model showed that the biosorption process of Cu (II) ions using dry biomass biosorbent Aphanothece sp. follows the Freundlich isotherm model with an R2 value of 0.9962.